Energy efficient heating : an overview - Jones, Phil (CIBSE, 2009)
This publication provides an introduction to energy efficient heating systems for engineers and building professionals that need an overview of the subject. -- Provided by publisher.
Keywords: Offices -- Heating and ventilation.; Hot-water heating.; Buildings -- Energy conservation.; elektronické knihy; electronic books